Factors Affecting Return to Play After Anterior Cruciate Ligament Reconstruction: A Review of the Current Literature. Issue 4 (November 2014) - Bauer, Matthew; Feeley, Brian T.; Wawrzyniak, John R.; Pinkowsky, Gregory; Gallo, Robert A.
Abstract : : Anterior cruciate ligament reconstruction has been reported to produce normal or near-normal knee results in > 90% of patients. A recent meta-analysis suggested that, despite normal or near-normal knees, many athletes do not return to sports. Rates and timing of return to competitive athletics are quite variable depending on the graft type, the age of the patient, the sport, and the level of play. Even when athletes do return to play, often they do not return to their previous level. Graft failure, subjective physical factors, and psychological factors, including fear of reinjury and lack of motivation, appear to play a large role in patients' ability to return to sporting activities.